Children with type 1-diabetes from ethnic minorities. Vulnerable patients needing a tailored medical support - Vanelli, M.; Cangelosi, A.M.; Fanciullo, et al., L. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim: Newly diagnosed children with type 1 diabetes from ethnic minorities are a growing presence in outpatient pediatric clinics, and are reported as a group at risk of poor metabolic control. In the present study we investigated the barriers affecting chances of minority diabetic children to achieve the same metabolic targets of native peers with type 1 diabetes. MaterialS and Methods: The study investigated 35 children from ethnic minorities (group 1) admitted to the Children University Hospital of Parma, Italy, from 1st January 2000 to December 31st, 2011, and data concerning current age, gender, ethnicity, age at diabetes onset, HbA1c, DKA severity degree at diagnosis, insulin therapy, annual number of out patient clinic visits, number of admissions for acute decompensation, and treatment cost. A short questionnaire on background, family situation, difficulties in diabetes monitoring, and outpatient clinic procedures completed the study. The results were compared with data collected from 30 matched native peers (group 2). Results: Mean HbA1c level at admittance was higher in Group 1 (11.8±1.0%) than in Group 2 (9.0±2.2%; p=0.000). The differences were confirmed when HbA1c mean cumulative values (8.6±2.1 vs 7.6±1.1; p=0.022) were calculated. Group 1 children at admission showed poorer metabolic conditions and longer stay at hospital (16±3 days) than Group 2 patients (8±2 days; p=0.000). The total costs for DKA treatment and family education resulted higher in Group 1 (+54%) than in Group 2 patients. Discontinuous capillary blood glucose monitoring and outpatient clinic visits missed were more frequent in Group 1 than in Group 2 patients. Thirteen patients in Group 1 needed a re-admittance to hospital because of a hypoglycemia (5 cases) or a hyperglycemia (8 cases). The same episodes were not recorded in Group 2 patients. Most of parents expressed the wish to be supported with educational material in their own language. Conclusions: Children with TDM belonging to an ethnic minority had poorer metabolic control compared with native patients. This results from several cultural, educational, economic deficiencies which influence their family life and probably reduced their chances to obtain a better control.